Analysis of the Implementation of PSAK 409, Transparency and Accountability of Financial Management in Optimizing Zakat Potential at the National Amil Zakat Agency (BAZNAS) East Lombok Regency - Sulastri, Maria; Lenap, Indria Puspitasari (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the application of PSAK 409, accountability, and transparency of fund management to optimize zakat revenue at BAZNAS East Lombok Regency. The research method used is qualitative, with a descriptive approach that includes observation, documentation, and interviews. The results showed that BAZNAS East Lombok Regency in its zakat accounting treatment was by PSAK 409, through financial position report, which separates zakat funds, Infaq /Alms, and non-zakat funds, and makes complete financial reports. Transparency, such as open accountability, accessibility, and publication of financial reports, has also been implemented. Regarding accountability, it has presented financial reports promptly, with complete financial report components. It has carried out financial report audits that can increase the trust of zakat givers and impact optimizing their zakat revenues.